Cochlear Implantation in Lithuania: Prevalence and System Overview - Mataitytė - Diržienė, Jurga; Stumbrys, Daumantas; Byčkova, Jekaterina; Lesinskas, Eugenijus (Socialinė teorija, empirija, politika ir praktika, 2018)
[only abstract and keywords in English; full article, abstract and keywords in Lithuanian]Previous researches have shown that cochlear implantation (or hearing implantation) together with hearing recovery program provides successful social integration for children with sensorineural hearing loss. Cochlear implantation is implemented from 1998 in Lithuania. About 377 people were implanted until the end of 2017. Vast majority of whom are children. Most of the studies carried out in this field are dealing with clinical or technical aspects. There is a lack of research related to aspects of health policy or social integration problems. We overview the system of cochlear implantation, prevalence, and patients’ pathway in this paper. We use a document analysis and descriptive statistics methodologies in this study. To the authors knowledge this is the first study overviewing cochlear implantation system in Lithuania.
Keywords: cochlear implantation, hearing loss, Lithuania